Gastrointestinal parasites of black grouse Lyrurus tetrix: A long-term study (1986–2019) in the French Alps. (July 2021) - Tizzani, Paolo; Fanelli, Angela; Belleau, Eric
Abstract: This study investigates the gastroenteric parasites community of 336 black grouse Lyrurus tetrix, covering a wide part of the totality of the species range in the French Alps and characterized by a long-term sampling (1986–2019). Parasite community was described using common epidemiological descriptors. Additionally, for the most prevalent parasite, a species distribution model (SDM) was built to understand the main factors influencing parasite occurrence. Ascaridia compar, Capillaria caudinflata, cestodes ( Raillietina urogalli, R.cesticillus, and Hymenolepis microps ), Eimeria sp. ( E. lyruri and E.nadsoni ), Corrigia corrigia and Acanthocephalus sp. The most prevalent species was C.caudinflata (P: 33%, CI95%: 28–38), whereas the lowest prevalence was recorded for Acantocephalus sp. (P:0.3%, CI95%:-0.3–0.9).The selected SDM for C.caudinflata includes only 3 variables: BIO11 (Mean Temperature of Coldest Quarter), the latitude of sampled animals and the distance from ski tour way. The distribution of C.caudinflata in the French Alps presents sharply defined areas where there are optimal environmental conditions for maintaining the life cycle of this parasite. These are the colder areas, characterized by higher latitude values and close to the ski tour ways. This study provides a valuable contribution to the scarce literature on wild Galliformes, describing the composition of the gastrointestinal parasite community of the black grouse. Highlights: This is one of the few works investigating the parasites community of Black grouse The most prevalent parasite species was Capillaria caudinflata ( P: 33%, CI95% 28–38) The northern part of the French Alps is at a high risk of C.caudinflata occurrence